Usulan Perbaikan Tata Letak Fasilitas Produksi Kue Kering di PT. Surya Indah Food Multirasa - Afrida Nur Aini; Raden Faridz; Iffan Maflahah (AGROINTEK, 2019)
ABSTRACT The design of facility layout in an industry becomes an important part of the production process. The layout of pastry facilities at “PT Surya Indah Food Multi rasa ” is expected not still give optimum production because of in non-sequential production flows that occur in the formation of dough, oven, squash and finished products. The purpose of the study was to make a layout that fits the order of process flow by designing through the Blocplan-90 application. The study was conducted in November 2018 until February 2019. The Blocplan method is one of an easy computer operating the system by using manually entering facility data. The data needed is in the form of a map of the operation process, a linkage diagram of activities. The results of the initial layout data processing resulted in R-Score 0.78 and the proposed improvement with automatic search resulted in R-Score 0.98. The design of the proposed improvement is more optimal with the value of R-Score approaching the value of 1(one). Changes in the layout of the facility occur in squash which is closer to mixing and weighing materials and oven facilities close to the finished product.